Peningkatan keterampilan memecahkan masalah soal cerita melalui model auditory, intellectually and repetition peserta didik kelas V sekolah dasar - Yosita Lisna Bella Astuti; Siti Kamsiyati; Fadhil Purnama Adi (Didaktika Dwija Indria, 2019)
The aim of the reseach is to improve the problem sklills by applying auditory, intellectually and repetition model in fifth grade students of Ampel 1 public elementary school 2018/2019 academic  year. This Classroom Action Research be composed of  three cycles with two meetings. Each cycles consist of four stages. The subjects of this study were teachers and 36 students. Data collecting techniques used observation, interview, documentation and test. Data validity used source and  technical triangulation. Data analysis used descriptive comparactive,critical analysis and interactive data analysis. The results showed that the average score of pre-action was 30.75 with classical completeness of 5,56% classical completeness increased to 51.08 with 19.4% classical completeness in first cycle and increased to 61.94 with classical completeness of 52.78% in cycle II, increased again in third cycle  to 82.67 with clasiccal completeness of 86.1%. The results of the research, it can be concluded that through the application of the Auditory Intellectually and Repetition (AIR) model can improve the problem solving skills in fifth grade of Ampel 1 Public Elementary School, Boyolali 2018/2019 academic year.Keyword : problem solving skills, auditory intellectually repetition model.